Post‐exercise carbohydrate and energy availability induce independent effects on skeletal muscle cell signalling and bone turnover: implications for training adaptation. (21st August 2019) - Hammond, Kelly M.; Sale, Craig; Fraser, William; Tang, Jonathan; Shepherd, Sam O.; Strauss, Juliette A.; Close, Graeme L.; Cocks, Matt; Louis, Julien; Pugh, Jamie; Stewart, Claire; Sharples, Adam P.; et al.
Abstract : Key points: Reduced carbohydrate (CHO) availability before and after exercise may augment endurance training‐induced adaptations of human skeletal muscle, as mediated via modulation of cell signalling pathways. However, it is not known whether such responses are mediated by CHO restriction, energy restriction or a combination of both. In recovery from a twice per day training protocol where muscle glycogen concentration is maintained within 200–350 mmol kg −1 dry weight (dw), we demonstrate that acute post‐exercise CHO and energy restriction (i.e. < 24 h) does not potentiate potent cell signalling pathways that regulate hallmark adaptations associated with endurance training. In contrast, consuming CHO before, during and after an acute training session attenuated markers of bone resorption, effects that are independent of energy availability. Whilst the enhanced muscle adaptations associated with CHO restriction may be regulated by absolute muscle glycogen concentration, the acute within‐day fluctuations in CHO availability inherent to twice per day training may have chronic implications for bone turnover. Abstract: We examined the effects of post‐exercise carbohydrate (CHO) and energy availability (EA) on potent skeletal muscle cell signalling pathways (regulating mitochondrial biogenesis and lipid metabolism) and indicators of bone metabolism. In a repeated measures design, nine males completed a morning (AM) and afternoon (PM) high‐intensity interval (HIT) (8 × 5 min at 85% V ̇ O 2 peak ) running protocol (interspersed by 3.5 h) under dietary conditions of (1) high CHO availability (HCHO: CHO ∼12 g kg −1, EA∼ 60 kcal kg −1 fat free mass (FFM)), (2) reduced CHO but high fat availability (LCHF: CHO ∼3 ( −1, EA∼ 60 kcal kg −1 FFM) or (3), reduced CHO and reduced energy availability (LCAL: CHO ∼3 g kg −1, EA∼ 20 kcal kg −1 FFM). Muscle glycogen was reduced to ∼200 mmol kg −1  dw in all trials immediately post PM HIT ( P <  0.01) and remained lower at 17 h (171, 194 and 316 mmol kg −1  dw) post PM HIT in LCHF and LCAL ( P <  0.001) compared to HCHO. Exercise induced comparable p38MAPK phosphorylation ( P <  0.05) immediately post PM HIT and similar mRNA expression (all P <  0.05) of PGC‐1α, p53 and CPT1 mRNA in HCHO, LCHF and LCAL. Post‐exercise circulating βCTX was lower in HCHO ( P <  0.05) compared to LCHF and LCAL whereas exercise‐induced increases in IL‐6 were larger in LCAL ( P <  0.05) compared to LCHF and HCHO. In conditions where glycogen concentration is maintained within 200–350 mmol kg −1  dw, we conclude post‐exercise CHO and energy restriction (i.e. < 24 h) does not potentiate cell signalling pathways that regulate hallmark adaptations associated with endurance training. In contrast, consuming CHO before, during and after HIT running attenuates bone resorption, effects that are independent of energy availability and circulating IL‐6. Key points: Reduced carbohydrate (CHO) availability before and after exercise may augment endurance training‐induced adaptations of human skeletal muscle, as mediated via modulation of cell signalling pathways. However, it is not known whether such responses are mediated by CHO restriction, energy restriction or a combination of both. In recovery from a twice per day training protocol where muscle glycogen concentration is maintained within 200–350 mmol kg −1 dry weight (dw), we demonstrate that acute post‐exercise CHO and energy restriction (i.e. < 24 h) does not potentiate potent cell signalling pathways that regulate hallmark adaptations associated with endurance training. In contrast, consuming CHO before, during and after an acute training session attenuated markers of bone resorption, effects that are independent of energy availability. Whilst the enhanced muscle adaptations associated with CHO restriction may be regulated by absolute muscle glycogen concentration, the acute within‐day fluctuations in CHO availability inherent to twice per day training may have chronic implications for bone turnover.